Cascading effects in freshwater microbial food webs by predatory Cercozoa, Katablepharidacea and ciliates feeding on aplastidic bacterivorous cryptophytes. Issue 10 (18th June 2020) - Šimek, Karel; Grujčić, Vesna; Mukherjee, Indranil; Kasalický, Vojtěch; Nedoma, Jiří; Posch, Thomas; Mehrshad, Maliheh; Salcher, Michaela M
ABSTRACT: Heterotrophic nanoflagellates (HNF) are considered as major planktonic bacterivores, however, larger HNF taxa can also be important predators of eukaryotes. To examine this trophic cascading, natural protistan communities from a freshwater reservoir were released from grazing pressure by zooplankton via filtration through 10- and 5-µm filters, yielding microbial food webs of different complexity. Protistan growth was stimulated by amendments of five Limnohabitans strains, thus yielding five prey-specific treatments distinctly modulating protistan communities in 10- versus 5-µm fractions. HNF dynamics was tracked by applying five eukaryotic fluorescence in situ hybridization probes covering 55–90% of total flagellates. During the first experimental part, mainly small bacterivorous Cryptophyceae prevailed, with significantly higher abundances in 5-µm treatments. Larger predatory flagellates affiliating with Katablepharidacea and one Cercozoan lineage (increasing to up to 28% of total HNF) proliferated towards the experimental endpoint, having obviously small phagocytized HNF in their food vacuoles. These predatory flagellates reached higher abundances in 10-µm treatments, where small ciliate predators and flagellate hunters also ( Urotricha spp., Balanion planctonicum) dominated the ciliate assemblage. Overall, our study reports pronounced cascading effects from bacteria to bacterivorous HNF, predatory HNF and ciliates in highly treatment-specific fashions, defined by both prey-food characteristics and feeding modes of predominating protists. Abstract : Presented are experimentally induced cascading effects from bacteria to bacterivorous flagellates, predatory flagellates and ciliates in different plankton size fractions, modulated by prey-food characteristics and feeding modes of predominating protists.